Early Surgery with Neuraxial Anaesthesia in Patients on Chronic Antiplatelet Therapy with a Proximal Femur Fracture: Multicentric Randomised Clinical Trial - Rafael Anaya (MDPI AG, 2021)
Background: Patients with proximal femur fracture on antiplatelet treatment benefit from early surgery. Our goal was to perform early surgery under neuraxial anaesthesia when indicated by the platelet function test. Methods: We conducted a multicentre randomised open-label parallel clinical trial. Patients were randomised to either early platelet function-guided surgery (experimental group) or delayed surgery (control group). Early surgery was programmed when the functional platelet count (as measured by Plateletworks) was >80 × 109/L. The primary outcome was the emergency admission-to-surgery interval. Secondary outcomes were platelet function, postoperative bleeding, medical and surgical complications, and mortality. Results: A total of 156 patients were randomised, with 78 in each group, with a mean (SD) age of 85.96 (7.9) years, and 67.8% being female. The median (IQR) time to surgery was 2.3 (1.5–3.7) days for the experimental group and 4.9 (4.4–5.6) days for the control group. One-third of patients did not achieve the threshold functional platelet count on the first day of admission, requiring more than one test. There was no difference in clinical outcomes between groups. Conclusions: A strategy individualised according to the platelet function test shortens the time to proximal femur fracture surgery under neuraxial anaesthesia in patients on chronic antiplatelet treatment. Better powered randomised clinical trials are needed to further evaluate the clinical impact and safety of this strategy.